KEMAMPUAN GURU DALAM MENGAJAR DENGAN MENGGUNAKAN SUPERVISI DI SDN 007 KAMPUNG BARU - Marwin Marwin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
A teacher is someone who should be a role model. This figure will look at the learning process in the class interact with the student directly so that the student can imitate what the teacher does, for that teacher’s ability teaching must be better. This research is school action research by supervising in a class by using a quantitative method description with the numbers described. The research sample is all the teachers with a total of 12 teacher’s in SDN 007 Kampung Baru Kecamatan Gunung Toar Kabupaten Kuantan Singingi. Research result in first supervision who gets a good category is 11 teacher’s and 1 teacher who get enough category, whit average 72.17, as long as second supervision is done who gets teacher’s data in teaching ability with very good category 6 teacher’s and 6 teacher’s with good category, with average 82.1. it can be concluded that with supervision done by the head master can give positive impact in teacher’s teaching ability.